Strategi Pengembangan Integrasi Usaha Hidroponik Jatinangor Urban Farming - Ayu, Karenza Rinjani; Renaldi, Eddy (Universitas Galuh, 2025)
Jatinangor Urban Farming is one of the urban farming business groups that originated from the utilization of unused land. In the beginning, Jatinangor Urban Farming only focused on the process of cultivation to hydroponic sales only. Over time, the owner and group members tried to integrate their business into a culinary and agro-education business. However, the main challenge faced by Jatinangor Urban Farming is the absence of an effective and structured development strategy as a guideline in integrating the business. So, this research was conducted to see the current condition of the Jatinangor Urban Farming business, by identifying internal and external environmental factors so as to form an appropriate alternative development strategy. The design and approach of this research is descriptive qualitative and case study. Data collection was carried out through interviews and observations to decision makers at Jatinangor Urban Farming consisting of 3 people, complemented by strengthening information data from 16 informants who had visited Jatinangor Urban Farming. Data analysis was carried out using the IFE, IFE, IE, SWOT, and QSPM matrixs. The calculation results show the total score on the IFE Matrix and EFE Matrix indicates the group's internal and external factors are above average. The current position of Jatinangor Urban Farming based on the IE matrix is in cell V, namely the position of the strategy to maintain and maintain (Hold and Maintain). Based on the SWOT matrix, four alternative strategies are obtained with the priority order of strategies in QSPM are (1) Strengthening business management and planning by building a more professional business management structure, (2) Innovative product development strategies and maximizing the use of business diversification (culinary and agroeducation), (3) Partnership and Market Expansion Strategies, (4) Improving branding through social media and doing digital marketing.